1976
DOI: 10.1071/ph760471
|View full text |Cite
|
Sign up to set email alerts
|

Australian Journal of Physics Astrophysical Supplement

Abstract: The fourth catalogue of radio sources observed at 408 MHz with the Molonglo radiotelescope is presented. A total of 1349 sources is listed to a limiting flux density of 0�2 Jy, the catalogue being largely complete above 0� 25 Jy. The area of sky surveyed includes the Magellanic Clouds as well as a comparison region of similar angular extent. Detailed notes are provided on some of the Cloud sources, and maps are given for complex sources in the region of the Clouds. Those sources for which high-frequency or opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…SNR 0450À70.9, on the other hand, has an [S ii]/H ratio of 0.7 and a radio spectral index estimated at À0.2 (S / ), which clearly confirm its identity as an SNR ( Mathewson et al 1985;Clarke et al 1976). The X-ray emission from SNR 0450À70.9 has never been detected; no pointed Einstein or ROSAT observations of this remnant were ever made.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…SNR 0450À70.9, on the other hand, has an [S ii]/H ratio of 0.7 and a radio spectral index estimated at À0.2 (S / ), which clearly confirm its identity as an SNR ( Mathewson et al 1985;Clarke et al 1976). The X-ray emission from SNR 0450À70.9 has never been detected; no pointed Einstein or ROSAT observations of this remnant were ever made.…”
Section: Introductionmentioning
confidence: 54%
“…We combined our flux density values with those of previous radio observations at various frequencies ( McGee et al 1972;Clarke et al 1976;Mathewson et al 1985;Filipovic et al 1995;Bock et al 1999) and used a linear regression fit (log frequency vs. log flux density) to obtain a spectral index for the SNR of À0.21 (Table 1, Fig. 6).…”
Section: Radio Emissionmentioning
confidence: 99%
“…The main source of uncertainty in the measured flux densities is the definition of the area best representing the SNR, which dominates the statistical error. Based on different trials, we estimate that the combined flux density errors from all radio images used in this study (apart from 73 cm where the error is in order of 20%; Mathewson et al 1983;Clarke et al 1976), are ∼10% at each given frequency. Using the flux densities from Table 1, we estimated spectral indices for the PWN (α Core = −0.04 ± 0.04), the outer SNR shell excluding the core (α Shell = −0.43 ± 0.01), and the whole SNR (α Total = −0.39 ± 0.03); see Fig.…”
Section: Radio-continuummentioning
confidence: 99%
“…Mathewson et al (1983) catalogued this object based on studies of optical and MOlonglo Synthesis Telescope (MOST) survey data, and reported an optical size of 140 × 131 . SNR J0453-6829 is also listed in the 408 MHz MC4 catalogue of Clarke et al (1976) as a distinctive pointlike radio source, for which Mathewson et al (1983) later remeasured a flux density of 350 mJy. Mills et al (1984) detected this source with specific MOST pointings and reported a rather flat spectral index of α = −0.38.…”
Section: Introductionmentioning
confidence: 99%
“…The Magellanic Cloud regions are those defined by Turtle & Amy (1991), i.e., 00 h 25 m < < 01 h 35 m , À74 40 0 < < À70 45 0 for the Small Magellanic Cloud and 04 h 46 m < < 05 h 58 m , À72 20 0 < < À65 10 0 for the Large Magellanic Cloud. Examination of the 408 MHz MC4 survey (Clarke et al 1976) reveals that the only sources in these regions with S 408 > 4:0 Jy are associated with the Clouds rather than being background objects. From the mean source density of MS4 (x 2.6) we would expect only two sources to lie in these regions, so a count of zero is not surprising.…”
Section: Definition Of the Ms4 Samplementioning
confidence: 99%